Strategic Public Relations Communication in Higher Education: The Case of Raden Fatah State Islamic University Palembang - Widodo, Rudianto (CHANNEL: Jurnal Komunikasi, 2024)
This study examines Raden Fatah State Islamic University Palembang's public relations (PR) communication strategies in establishing relationships with press agencies. The research highlights the challenges and opportunities faced by the university's PR department in navigating the rapidly evolving digital landscape. Utilizing a qualitative approach and case study methodology, the study explores the university's cooperative efforts with mass media outlets, focusing on internal and external stakeholders. Key findings indicate that effective PR strategies involve strategic communication, media engagement, and proactive crisis management. The study also identifies inhibiting factors, such as interest conflicts and coordination issues, alongside supportive factors like robust Information and Communication Technology (ICT) infrastructure and collaborative media partnerships. These insights provide a comprehensive understanding of the PR practices at Raden Fatah State Islamic University and offer actionable recommendations for enhancing institutional communication strategies.